(untitled) (Communications in Computational Physics, 2020)
We employ the lattice Boltzmann method and random walk particle tracking to simulate the time evolution of hydrodynamic dispersion in bulk, random, monodisperse, hard-sphere packings with bed porosities (interparticle void volume fractions) between the random-close and the random-loose packing limit. Using Jodrey-Tory and Monte Carlo-based algorithms and a systematic variation of the packing protocols we generate a portfolio of packings, whose microstructures differ in their degree of heterogeneity (DoH). Because the DoH quantifies the heterogeneity of the void space distribution in a packing, the asymptotic longitudinal dispersion coefficient calculated for the packings increases with the packings' DoH. We investigate the influence of packing length (up to 150 dp, where dp is the sphere diameter) and grid resolution (up to 90 nodes per dp) on the simulated hydrodynamic dispersion coefficient, and demonstrate that the chosen packing dimensions of 10 dp×10 dp×70 dp and the employed grid resolution of 60 nodes per dp are sufficient to observe asymptotic behavior of the dispersion coefficient and to minimize finite size effects. Asymptotic values of the dispersion coefficients calculated for the generated packings are compared with simulated as well as experimental data from the literature and yield good to excellent agreement.